Analisis Strength, Weakness, Opportunities, Threats di Rumah Makan Sutan Mudo Sakato (SMS) Desa Sebapo, Mestong Jambi Untuk Meningkatkan Daya Saing - Miftakhul Jannah; Agustina Mutia; Bella Arisha (Universitas Sains dan Teknologi Komputer, 2023)
The culinary business is the fastest growing business because food is everyone's basic needs. Competitiveness is the company's ability to be compete to maintain the business to be superior to its competitors in seizing attention and consumer loyalty in order to generate sustainable profits. SWOT analysis is a strategic planning method used to evaluate external and internal factors of a business speculation. To increase the competitiveness of the House Eating SMS needs to determine the most accurate and competitive marketing strategy. The research method used is qualitative. Informants in this study are owners, employees, and customers of Rumah Makan SMS. The results of this study show that the strength of SMS Restaurant's business lies in the taste of typical Minang dishes, strategic location, has regular customers, relatively cheap prices compared to closest competitors. The weakness of the SMS Restaurant is that when the price of groceries rises, the service is less fast. The opportunity that Rumah Makan SMS has is the opening of a new branch. Home Threat Eating SMS comes from culinary business rivals of the same or not the same type small eatery. Based on the results of the SWOT analysis of the strategies required for to increase competitiveness is the addition of a new menu, the addition of the number of employees.